Effectiveness of the Culturally Responsive Instruction (CRI) Package on Teachers’ Comprehension of Culturally Responsive Behaviours - Ravindra Kumar; Ravi Kant (International Journal of Education Sciences, 2025)
India is a country of great cultural heritage, as seen in its art, literature, traditions, languages, and historical sites. Its diversity and vitality make it a unique place on the world map, drawing individuals from across the globe through tourism, festivals, yoga, and classical literature. Every state in India has its own distinct cultural and linguistic identity. Consider Bihar, for instance—it has been a key player in the educational history of the world, with ancient centres of learning such as Nalanda University and Taxila University being a testament to its intellectual heritage. This research aimed to explore how a Culturally Responsive Instruction (CRI) package can assist school teachers in embracing more culturally responsive teaching practices. The study employed pre-test and post-test control group design and had 68 teachers from six schools in Gaya district, Bihar. Experimental group teachers were oriented to apply the CRI package, which entails interactive and hands-on activities to inculcate culturally responsive behaviours. On the other hand, the control group continued with traditional teaching practices. To assess the teachers’ culturally responsive behaviours, the Culturally Responsive Instruction Scale (CRIS) was employed by the researchers. Through a t-test analysis, the study found that teachers who were oriented for implementing the CRI package improved significantly over teachers using conventional teaching techniques, particularly in curricular and co-curricular aspects. The results point to the fact that incorporating the CRI package in teaching practices can more effectively prepare teachers to develop an inclusive and culturally responsive learning environment.
Keywords: Culturally responsive instruction; co-curricular aspects; curricular aspects